Laporan Keuangan Kelompok Tani Srirejeki Ii Berdasarkan Isak 35 - Fransiska Wahyu Lestari (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2022)
Financial statements for non-profit entities are prepared based on accounting standards that contain non-profit entities. The preparation of non-profit-oriented entity reports is regulated in the Interpretation of Financial Accounting Standards (ISAK) No. 35. This study aims to analyze and present the financial statements of the Sri Rejeki II farmer group based on ISAK 35. The method used in this research is descriptive qualitative method. The results in this study are to reconstruct the financial statements owned by the Sri Rejeki Farmers Group in Gunung Pasir Jaya Village using ISAK 35 financial standards in the form of Comprehensive Income Statements, Statements of Changes in Net Assets, Statements of Financial Position, Cash Flow Statements and Notes to Financial Statements (CALK).